2013
DOI: 10.1517/13543784.2013.793307
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines for the treatment of gastrointestinal cancers: clinical experience and new perspectives

Abstract: The complexity of the immune system and the unfavorable pharmacokinetic properties of cytokines limit the efficacy of these molecules as single agents for the treatment of cancer. Expression from gene therapy vectors, together with new methods of targeting and stabilization, may overcome these hurdles. We believe cytokines will play a crucial role as part of combined approaches, enhancing the action of adoptive cell immunotherapy, oncolytic viruses or biological therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Therapeutic approaches employing cytokines, immune checkpoint inhibitors, and chimeric antigen receptor T cells (CAR-T) are commonly employed. Cytokines, such as IFNα, IFNγ, IL-2, and GM-CSF, which induce B cells, T cells, NK cells, and macrophages for tumor cell killing, have been successfully used for gastrointestinal cancer treatment [153]. The two immune checkpoint inhibitors target PD-1/PD-L1 and CTLA4.…”
Section: Immunotherapymentioning
confidence: 99%
“…Therapeutic approaches employing cytokines, immune checkpoint inhibitors, and chimeric antigen receptor T cells (CAR-T) are commonly employed. Cytokines, such as IFNα, IFNγ, IL-2, and GM-CSF, which induce B cells, T cells, NK cells, and macrophages for tumor cell killing, have been successfully used for gastrointestinal cancer treatment [153]. The two immune checkpoint inhibitors target PD-1/PD-L1 and CTLA4.…”
Section: Immunotherapymentioning
confidence: 99%
“…Cytokines are secreted proteins used by immune system cells for intercellular communication. A number of them have potent immunostimulatory and antineoplastic activities in animal models and the results of several Phase I and II clinical trials in patients with gastrointestinal cancer have been reported and recently reviewed [47]. IFN-α was initially considered a promising treatment for cancer -and specifically for HCC -due to its antiproliferative, proapoptotic and immunomodulatory activities.…”
Section: • • Cytokinesmentioning
confidence: 99%